Synthesis and Characterization of Modified Chitosan-based Novel Superabsorbent hydrogel: Swelling and Dye Adsorption behavior - Oladipo, Akeem Adeyemi (Eastern Mediterranean University (EMU), 2011)
ABSTRACT: Lately, a wide application of eco-friendly polysaccharide-based hydrogels in waste water treatment has received enormous attention in the literature. Particularly, the development of super swelling chitosan-based materials as versatile and useful adsorbent polymeric agent is an expanding area in the field of adsorption science today. The effluents containing dye materials from the processing industries are washed off into rivers and lakes which can be very harmful to creatures. Low-cost biopolymers and biodegradable adsorbents have been researched to be a good tool to minimize the environmental hazards caused by the industrial effluents by removal of these toxic and carcinogenic dyes from the waste effluents. In this work, a novel superabsorbent hydrogel was synthesized using water-soluble glycidyl methacrylated N, O-(2, 3 dihydroxypropyl) chitosan (DHPC-GMA) and acrylamide (AAm) as reactants. A feasible synthesis was achieved due to the incorporation glycidyl methacrylate (GMA) into the structure of water soluble chitosan, N, O-(2, 3 dihydroxypropyl), (DHPC) to form the water soluble chitosan-methacrylated (DHPC-GMA), in a calculated mixture of water-DMSO as solvent and TEMED as catalyst. Thereafter, the DHPC-GMA was copolymerized in potassium persulfate aqueous solution with AAm yielding superabsorbent (DHPC-GMA-g-PAAm) hydrogel. The incorporation of GMA on DHPC molecules was confirmed by FTIR by the presence of a band at 1637cm-1 indicative of C=C stretching frequency and strong broad band in the region 1711-1641 cm-1 in DHPC-GMA-g-PAAm hydrogel spectrum attributed to the overlap of the C=O stretching bands of esters of DHPC-GMA, primary amides and N-H deformation of primary amide from AAm indicating copolymerization of DHPC-GMA with AAm. The maximum grafting percentages (%G) and grafting efficiency (%E) for hydrogel sample B, C and D with varying monomer (AAm) concentration are %G; 150, 304, 995 and %E; 49.8, 60.8, 99.5 respectively. The synthesized hydrogel shows super swelling ability with swelling percentage of about 1900% and the swelling kinetic fits well with second-order- kinetic model. A batch system was applied to study the adsorption behavior of Reactive blue 2 (RB2), Erichrome Black T (EBT) and mixture of both dyes in aqueous solution by the DHPC-GMA-g-AAm hydrogel. The adsorption capacities were 38.02mg/g EBT and 32.73mg/g RB2 for sample D with highest grafting percentage and 12.79mg/g EBT and 58.14mg/g RB2 for sample B with the lowest grafting percentage. The adsorption of both single and mixture of dyes onto the hydrogel fit with the second-order kinetic model and the kinetic data is in good agreement with the experimental data having high correlation coefficients (R2 = 0.999). The competitive adsorption favored the dye EBT in the mixture solution and the percentage removal of EBT reaches 63.4% at 48 hr contact time which is larger than 36.5% of RB2 in same solution. Keywords: Superabsorbent hydrogel, characterization, erichrome black T, reactive blue 2, competitive dye adsorption, water-soluble chitosan. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Son zamanlarda, doğa dostu polisakkarit bazlı hidrojellerin biyomedikal alanlarda ve atık su iyleşmelerindeki geniş uygulamaları literatürde büyük önem görmektedir. Özellikle, çok yönlü ve kullanışlı absorban polimerik ajan olarak, süper şişen kitosan bazlı malzemelerin geliştirilmesi, bugünkü adsorpsiyon bilim alanında gelişen bir alandır. Endüstriyel proseslerden çıkan boya içerikli malzeme atıkların nehir ve göllere atılımı calılar için oldukca zararlıdır. Endüstriyel atıkların sebep olduğu bu toksik ve kanserojenik boyaların giderimi için düşük maliyetli biyopolimerler ve biyoparçalanabilir adsorbentler iyi birer araçtırlar. Bu çalışmada, kimyasal olarak modifiye edilmiş, suda çözülebilen glisidil metakrilatlanmış N, O-(2, 3 dihydroksipropil) kitosan (DHPC-GMA) ile akrilamid (AAm) reaktifleri kullanılarak, yeni bir süperabsorbent hidrojel sentezlenmiştir. Su-DMSO karışımı ve TEMED katalizörü varlığında glisidil metakrilatın (GMA), suda çözülebilen N, O-(2, 3 dihydroksipropil) kitosan (DHPC) ile birleşimi ile suda çözülebilen metakrilatlanmış kitosan (DHPC-GMA) formunun sentezi başarılmıştır. Daha sona, potasiyum persülfat çözeltisinde DHPC-GMA ile AAm kopolimerleştilerek süperabsorban (DHPC-GMA-g-PAAm) hidrojel ürünü elde edildi. DHPC molekülüne GMA’nın eklenmesi FTIR spektroskopideki 1637cm-1 deki bandın varlığı C=C gerilme frekansını göstermesiyle onaylanırken, DHPC-GMA-g-PAAm hidrojel spektrumunda 1711-1641 cm-1 bölgesindeki geniş güçlü bandın DHPC-GMA’nın ester grubunun C=O gerilme bandı, birincil amid ve AAm’in birincil amidinin N-H deformasyonu ile örtüşmesi DHPC-GMA ile AAm kopolimerizasyonu göstermektedir. Çeşitli monomer (AAm) konsantrasyonlu B,C ve D hidrojel örneklerinin, maksimum aşılanma yüzde (%G) ve aşılanma etkinlikleri (%E) sırası ile %G; 150, 304, 995 ve %E; 49.8, 60.8, 99.5’dir. Sentezlenmiş hidrojeller yaklaşık 1900 % şişme yüzdeli süper absorpsiyon yeteneği göstermekte ve kinetik şişmesi ikinci dereceden kinetik modelle örtüşmektedir. Reaktif mavi 2 (RB2), Erikrom siyah T (EBT) ve her ikisinin karışımının sulu çözeltilerinin DHPC-GMA-g-PAAm hidrojelleri tarafından adsorpsiyon davranış çalışmaları için batch sistemi uygulanmıştır. Yüksek aşılanma yüzdesine sahip D örneğinin adsorpsiyon kapasitesi EBT için 38.02mg/g ve RB2 için 32.73mg/g iken düşük aşılanma yüzdesine sahip D örneğinin adsorpsiyon kapasitesi EBT için 12.79mg/g ve RB2 için 58.14mg/g olarak belirlenmiştir. Hidrojeller üzerinde her iki boyanın tek başlarına ve karışım olarak adsorpsiyonu ikinci dereceden kinetik modele uymakta ve kinetik veriler deneysel verilerle yüksek korelasyon katsayıyla (R2 = 0.999) örtüşmektedir. Rekabetçi adsorpsiyonda, karışım çözeltisindeki EBT boyası tercih edilmekte ve 48saatlik etkileşim süresinde yüzde giderim %63.4 EBT, % 36.5 RB2 olmaktadır. Anahtar kelimeler: Süperabsorban h idrojel; karakterizasyon; erikrom siyah T; reaktif mavi 2; suda-çözülür kitosan; rekabetçi boya adsorpsiyonu.
Master of Science in Chemistry. Thesis (M.S)-- Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2011. Supervisor: Asist. Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Superabsorbent Hydrogel - Characterization - Erichrome Black T; Reactive Blue 2 - Competitive Dye Adsorption - Water-Soluble Chitosan